Genome-Wide Identification and Expression Analysis of Hexokinase Gene Family Under Abiotic Stress in Tomato - Jing Li; Xiong Yao; Jianling Zhang; Maoyu Li; Qiaoli Xie; Yingwu Yang; Guoping Chen; Xianwei Zhang; Zongli Hu (Plants)
In plants, hexokinase (HXK) is a kind of bifunctional enzyme involved in sugar metabolism and sugar signal transduction that plays important roles in plant growth and development and stress response. Some HXK genes without a phosphorylation function have been found in Arabidopsis, tobacco, etc., but these genes have not been identified in tomato. Therefore, further genome-wide systematic identification and characterization is necessary for tomato HXK genes. In this study, six HXK genes were identified from the tomato genome distributed across six different chromosomes, named SlHXK1-6. Gene structure analysis showed that the SlHXK genes contain the same number of introns and exons. Gene duplication and collinearity analysis revealed two pairs of tandem repeats among SlHXKs, and a higher collinearity between tomatoes and potatoes were found. Response elements associated with phytohormones, abiotic stresses, and growth and development were identified in the promoter sequences of SlHXKs. Quantitative real-time PCR (qRT-PCR) results further indicated the potential role of SlHXKs in tomato development and stress responses. The expression levels of most SlHXKs were significantly induced by abiotic stress, hormone, and sugar solution treatments. In particular, the expression of SlHXK1 was significantly induced by various treatments. Functional complementation experiments were performed using HXK-deficient yeast strain YSH7.4-3C (hxk1, hxk2, and glk1), and the results showed that SlHXK5 and SlHXK6 were unable to phosphorylate glucose and fructose in yeast. In conclusion, these results provide valuable foundations for further exploring the sugar metabolism and sugar signal transduction mechanisms of HXK and the functions of SlHXK genes in various abiotic stresses, and some SlHXKs may be key genes for enhancing plants’ tolerance to abiotic stresses.